Assessing The Impact Of Fiscal Shocks On Output In MENAP Countries - Cerisola, Martin (Technical Notes and Manuals; Technical Notes and Manuals ;, 2015)
This note is a reference guide to the econometric work on fiscal multipliers for MENAP countries. Spending and tax multipliers are estimated from conventional VAR models and identified using a sign-restrictions approach. Estimates show that fiscal multipliers tend to be small, except for those associated with government investment spending, which generally exceed unity. For the average MENAP country, fiscal multipliers for current spending, government consumption and government investment spending are 0.5, 0.8, and 1.1,respectively, while the tax revenues multiplier is estimated at around -0.4. There is also significant variation in the size of these multipliers across countries, consistent with differences in economic fundamentals, such as openness to trade and the flexibility of the exchange rate. The estimated multipliers are generally consistent with theoretical priors, and are in line with the evidence from the literature for other economies and categories of spending and taxes.